2016
DOI: 10.3354/ab00653
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive dynamics of the southern pink shrimp Farfantepenaeus subtilis in northeastern Brazil

Abstract: This study focused on the reproductive dynamics of southern pink shrimp Farfantepenaeus subtilis populations off the coast of Pernambuco, northeastern Brazil. F. subtilis specimens were collected each month between August 2011 and July 2012 by an artisanal fishing vessel. A total of 1246 specimens were collected, of which the majority (56%) were females, and which were significantly larger than the males. Ovary maturation, based on histological and visual criteria, was classified into 4 stages -I: immature, II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
2
13
0
1
Order By: Relevance
“…In the present study, the coloration for P. schmitti in the immature and spawned stages was translucent and these were the most difficult stages to be differentiated, especially in females of intermediate sizes, due to the similarity in characteristics and for presenting the same coloration. The same difficulty was reported for P. schmitti in Pernambuco [8], in São Paulo [12], and for other species of penaeids shrimps [12,[18][19][20]22,23].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In the present study, the coloration for P. schmitti in the immature and spawned stages was translucent and these were the most difficult stages to be differentiated, especially in females of intermediate sizes, due to the similarity in characteristics and for presenting the same coloration. The same difficulty was reported for P. schmitti in Pernambuco [8], in São Paulo [12], and for other species of penaeids shrimps [12,[18][19][20]22,23].…”
Section: Discussionsupporting
confidence: 68%
“…The emergence of peripheral bodies (PB) is the main factor that indicates that the ovary is in complete development, and characterizes its mature stage. Gonçalves et al [12] and Craveiro et al [9] demonstrated clear differentiation of cell structure by the presence of PB in the mature ovary of P. schmitti, which was corroborated in the study of gonadal development of other penaeid shrimps [20][21][22][23]. Peripheral bodies were observed in spherical to oval shapes, but can also be found in the form of rods for P. schmitti [8,11].…”
Section: Discussionmentioning
confidence: 67%
“…The main bioecological difference between species, discriminated by hypothetical-deductive knowledge, is related to migration. White shrimp (P. schmitti) and pink shrimp (P. subtilis) need the estuary to complete the life cycle [38,39,75,76], while the seabob shrimp (X. kroyeri) completes its life cycle exclusively at sea [33,40,77]. Another difference between species is the age at rst maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the region have shown that most of the catch (bycatch and target) of the shrimp fishery in Pernambuco occurs in the same area and share the same reproduction season, i.e. between October and March (Lopes et al, 2014(Lopes et al, , 2017Silva et al, 2015aSilva et al, ,b, 2016. Hence, the establishment of Marine Protect Areas (MPA) or a fishery-closing period should improve the conservation of the species and marine habitats exploited by this fishery in Pernambuco.…”
Section: Discussionmentioning
confidence: 99%